Dietary hydrolyzable tannins reduce growth performance and induce histological damage of Chinese seabass (Lateolabrax maculatus) - Qiu, Jianqiang; Huang, Wen; Cao, Junming; Zhao, Hongxia; Chen, Bing; Jiun-Yan, Loh; Peng, Kai (Frontiers in Marine Science, 2023)
Chinese seabass (Lateolabrax maculatus) is a popular carnivorous fish with delicious taste. Although the feed value of condensed tannins has been well documented for L. maculatus, information about the effects of hydrolyzable tannins (HTs) on the growth and health of L. maculatus is limited. This study was conducted to assess the effects of dietary HTs on growth performance, body composition, intestinal digestive enzyme activities, serum metabolites, antioxidant and immune response, and intestine and liver morphology of L. maculatus. A total of 640 fish were randomly divided into four groups with four replicates per group and 40 fish per replicate. Four diets were prepared to contain 0 (G0), 1 (G1), 2 (G2), and 4 (G4) g/kg of HTs. Fish were fed to apparent satiation twice a day during the 56-day feeding trial. Results showed that the final body weight, weight gain rate, specific growth rate, and feed intake were linearly decreased (p< 0.001) as dietary HTs increased. All fish had similar (p > 0.05) whole body compositions. Fish fed G2 and G4 had lower (p< 0.05) intestinal trypsin and lipase activities than those fed G0 and G1, whereas G4 had higher (p< 0.05) aspartate aminotransferase and alanine aminotransferase activities than G0. Serum total antioxidant capacity and lysozyme were linearly decreased (p< 0.01), but the malondialdehyde concentration was linearly increased (p< 0.01) as dietary HTs increased. Intestinal villi in G2 and G4 showed increased deformation, and the vacuolation of liver cells began to appear in G1 and was aggravated as dietary HTs increased. This study showed that HTs should be used with caution due to their growth-inhibiting effect, and the dietary HT level for L. maculatus is recommended to be less than 1 g/kg.